2019
DOI: 10.1159/000504608
|View full text |Cite
|
Sign up to set email alerts
|

Bortezomib- and Lenalidomide-Based Treatment of Refractory Plasmablastic Lymphoma

Abstract: <b><i>Introduction:</i></b> Plasmablastic lymphoma (PBL) is a rare variant of diffuse large B-cell lymphoma for which no optimal treatment has been established and prognosis remains poor. Here, we describe a human immunodeficiency virus-uninfected patient with PBL that was refractory to conventional chemotherapies but was successfully controlled with a bortezomib-based regimen followed by a lenalidomide-based regimen. <b><i>Case Presentation:</i></b> A 64-year-ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…Our shRNA screen showed that shRNAs targeting IRF4 appeared among the most toxic ones in our plasmablastic cell line model. Correspondingly, treatment with lenalidomide, that has been shown to downregulate IRF4 expression 24 , induced cytotoxicity in PBL-1 cells confirming promising case reports using lenalidomide for the treatment of patients with chemorefractory PBL 45,46 .…”
Section: Discussionmentioning
confidence: 56%
“…Our shRNA screen showed that shRNAs targeting IRF4 appeared among the most toxic ones in our plasmablastic cell line model. Correspondingly, treatment with lenalidomide, that has been shown to downregulate IRF4 expression 24 , induced cytotoxicity in PBL-1 cells confirming promising case reports using lenalidomide for the treatment of patients with chemorefractory PBL 45,46 .…”
Section: Discussionmentioning
confidence: 56%
“…These two patients achieved an OS of 18 months and 24 months. Very recently, Ando et al presented a case of a 64-year-old man with HIV-negative PBL refractory to conventional chemotherapy [ 54 ]. This patient responded to CyBorD (bortezomib, cyclophosphamide, dexamethasone), followed by lenalidomide/dexamethasone with a partial remission over 2 years.…”
Section: Introductionmentioning
confidence: 99%
“…Without specific care for PBL, intensive regimen like EPOCH only had 47.4–62.0% CR in fit patients ( 14 ). However, some reports of small-scale cases showed anti-PBL activity of non-cytotoxic agents such as bortezomib and lenalidomide ( 15 ). The prognosis of PBL patients is generally poor, with a median overall survival (OS) of 6–19 months ( 4 ).…”
Section: Discussionmentioning
confidence: 99%